Oleic Acid Protects against Hepatic Ischemia and Reperfusion Injury in Mice by Inhibiting AKT/mTOR Pathways. (13th December 2019) - Guo, Jianrong; Zhang, Tao; Gu, Jian; Cai, Kailin; Deng, Xiuling; Chen, Ke; Huang, Kun; Wang, Guobin; Li, Huili; Wang, Jiliang
Abstract : Hepatic ischemia-reperfusion (I/R) injury is a serious complication in patients who have undergone hepatic surgery such as orthotopic liver transplantation and partial hepatectomy. Recently, a new cytoprotective agent, ursodeoxycholyl lysophosphatidylethanolamide (UDCA-LPE), was reported to protect against hepatic I/R injury. However, the protective mechanism of UDCA-LPE is not fully understood. Therefore, we conducted this study to explore its underlying mechanism. We used liquid chromatography-tandem mass spectrometry (LC-MS/MS) to analyze the liver lipid metabolism changes in mice during I/R. KEGG enrichment indicated that UDCA-LPE is likely to exert its protective role by regulating fatty acid (FA) metabolism. Further analysis found that UDCA-LPE significantly increased the ratio of oleic acid (OA) to palmitic acid (PA). We found that mice pretreated with OA improved tolerance to hepatic I/R injury. In addition, the phosphorylation level of AKT was markedly upregulated during oxidative stress to promote p65 nuclear translocation, triggering an inflammatory response that exacerbated cell damage and OA treatment significantly inhibited this process. Notably, OA was found to inhibit H2 O2 -induced oxidative stress, inflammation, and cell death in HepG2 cells. Furthermore, we found that OA supplementation to the medium did not result in a significant increase in intracellular OA, but marked increase in the ratio of OA to PA, which may be an important mechanism for the inflammatory response induced by oxidative stress during I/R. Finally, we demonstrated that OA increased the level of autophagy in HepG2 cells, which may be one of the protective mechanisms against oxidative stress. Collectively, this study revealed that FA metabolism functionally determines the oxidative stress-related inflammation caused by hepatic I/R. We hypothesize that OA treatment may be a promising strategy for preventing and treating I/R-induced liver damage.